The influence of interpersonal synchrony on helping behavior, social bonding, and empathy in children - Holt, Mykaela (My University, 2019)
In the current study the influence of interpersonal synchrony on children’s empathy and helping behavior will be explored in typically developing children ages 3-12 years. In a replication of a spontaneous helping task developed by Kirschner & Tomasello (2010) fish food is spilt on the way to a fish tank, creating an opportunity for helping behaviour to occur at the cost of immediate gratification for the other child. Cognitive and affective empathy will be measured in an emotion assessment task using a 7-point Likert scale. We will also examine how the age of peer playmates affect these outcomes.
Presented on April 23, 2019 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: interpersonal synchrony; children